Relational Territorialities: Environmental Conflicts and Cosmopolitics in Western and Northern Mexico - BENCIOLINI, Maria (Frontera Norte, 2017)
This paper suggests considering the cosmo-political proposal made by some authors as a possible analytical framework for the study of socio-environmental conflicts involving indigenous peoples. By exploring ethnographic examples of western and northern Mexico, this article shows how the territoriality inhabited by indigenous peoples should be conceived in relational terms, and its component elements cannot be thought of as exploitable resources, the paper also described how the political demands of indigenous peoples are based on the network their embedded relationships whith humans, deities, ancestors, etc.